Current perspective on uniportal and multiportal video-assisted thoracic surgery during lobectomy for lung cancer - Danilo Coco; Silvana Leanza (Termedia Publishing House, 2022)
Non-small cell lung cancer (NSCLC) is the most typical type of lung cancer, and it is the leading cancer-related mortality globally. Lobectomy for early-stage NSCLC has been characterized in the previous decade using a wide range of methodologies. The development of video-assisted thoracoscopic surgery (VATS) allowed surgeons first to reduce the thoracotomy size, which is generally anterior, limiting it to trocar incisions or a single portal approach. This review aimed to describe current perspectives on operative outcomes, lymph node removal, oncologic outcomes, and advantages for surgeons performing uniportal VATS (uVATS) and multiportal (mVATS) lobectomy. The advantages of uVATS include comfortable operating for surgeons with a direct view and safety, and for patients more favourable operative outcomes. Also, the uVATS approach has previously been demonstrated to be effective and safe, with positive outcomes not just with respect to cosmetics but also in terms of a speedy recovery. Oncological uVATS clearance is comparable to multiportal VATS with respect to early mid-term survivability as well as nodal staging, as per retrospective comparison studies. However, the interpretation of outcomes must be made cautiously due to selection bias as well as lack of long-term follow-up; the choice of which VATS approach to utilize for patients' treatment following pulmonary resection is largely based on the preferences of the surgeon. As a result, it is difficult to say if one VATS method is better than another.